Analysis of Reputation Factors for the Personal Branding of Journalists in Thailand - Cholticha Rodgunphai; Jantima Kheokao (Asian Journal for Public Opinion Research)
This research is a combination of qualitative and quantitative methods. It analyzed reputation factors for the personal branding of journalists in Thailand. Research tools were in-depth interviews and an online questionnaire with 33 variables. Eleven journalists and informed sources were interviewed. A total of 1,262 survey respondents were divided into three groups including 586 recipients, 416 news people, and 260 academics. Data were analyzed using content analysis and factor analysis.